Duration of Dual Antiplatelet Therapy in Patients With Acute Coronary Syndrome Treated With New Generation Stents: A Meta-Analysis of Randomized Controlled Trials - Zhang, Wen-Jiao; Qiao, Xuan; Guo, Wen-Fen; Liang, Xi-Ying; Li, Yan; Wang, Zhi-Lu (Frontiers in Cardiovascular Medicine, 2021)
Background and objective: The optimum duration of dual antiplatelet therapy (DAPT) remains uncertain in patients with acute coronary syndrome treated with new generation stents. This meta-analysis was performed to investigate ischemia and bleeding outcomes with different DAPT strategies. Methods: PubMed, Embase, Cochrane and Web of science from inception to May 27, 2020, were systematically searched. Randomized controlled trials were included to compare short-term (6 months or less) with standard (12 months) DAPT in patients with acute coronary syndrome treated with new generation stents. The primary endpoints were myocardial infarction, definite or probable stent thrombosis and major bleeding. The secondary endpoints included all-cause death, cardiovascular death, stroke, target vessel revascularization and net adverse clinical events. Random effect model and fixed effect model were used to calculate the odds ratio (OR) and 95% confidence interval (CI) of each endpoint. Results: Four randomized controlled trials and seven subgroup analyses of larger randomized controlled trials, including a total of 21344 patients with acute coronary syndrome, met our inclusion criteria. The shorter DAPT was associated with significantly lower major bleeding compared with the standard DAPT (OR 0.71, 95% CI 0.56-0.90, P = 0.005, I2 = 25%), while without increasing the risk of myocardial infarction (OR 1.18, 0.88-1.58, P = 0.28, I2 = 20%), definite or probable stent thrombosis (OR 1.60, 0.98-2.59, P = 0.06, I2 = 0%). No significantly difference was observed in the risk of all-cause death (OR 0.96, 0.72-1.27, P = 0.76, I2 = 2%), cardiovascular death (OR 0.91, 0.62-1.33, P = 0.62, I2 = 0%), stroke (OR 0.84, 0.54-1.30, P = 0.43, I2 = 0%), target vessel revascularization (OR 1.14, 0.84-1.55, P = 0.41, I2 = 8%), and net adverse clinical events (OR 0.93, 0.80-1.07, P = 0.3, I2 = 18%) between the two groups. Conclusions: In patients with acute coronary syndrome treated with new generation stents, the shorter DAPT leads to a marked reduction in the risk of major bleeding compared with the standard DAPT. This benefit is achieved without increasing the risk of mortality or ischemic outcomes. The study protocol was registered in PROSPERO (CRD42020189871).